The commonness of rarity: Global and future distribution of rarity across land plants - Enquist, Brian J; Feng, Xiao; Boyle, Brad; Maitner, Brian; Newman, Erica A; Jørgensen, Peter Møller; Roehrdanz, Patrick R; Thiers, Barbara M; Burger, Joseph R; Corlett, Richard T; Couvreur, Thomas L P; Dauby, Gilles; et al. (Science advances, 2019)
A key feature of life's diversity is that some species are common but many more are rare. Nonetheless, at global scales, we do not know what fraction of biodiversity consists of rare species. Here, we present the largest compilation of global plant diversity to quantify the fraction of Earth's plant biodiversity that are rare. A large fraction, ~36.5% of Earth's ~435,000 plant species, are exceedingly rare. Sampling biases and prominent models, such as neutral theory and the k-niche model, cannot account for the observed prevalence of rarity. Our results indicate that (i) climatically more stable regions have harbored rare species and hence a large fraction of Earth's plant species via reduced extinction risk but that (ii) climate change and human land use are now disproportionately impacting rare species. Estimates of global species abundance distributions have important implications for risk assessments and conservation planning in this era of rapid global change.
Keywords: extinkce biologická; vyšší rostliny; Endangered Species; biodiverzita; Climate Change; Extinction, Biological; Embryophyta; ohrožené druhy; klimatické změny; Biodiversity